A psycho-social-environmental lens on radon air pollutant: authorities’, mitigation contractors’, and residents’ perceptions of barriers and facilitators to domestic radon mitigation - Hevey, David; Perko, Tanja; Martell, Meritxell; Bradley, Gary; Apers, Sofie; Rovenská, Kateřina Navrátilová (Frontiers in Public Health, 2023)
Radon is a major indoor air pollutant that poses a significant risk of lung cancer to those exposed in their homes. While mitigation of high radon levels in homes has been shown to be effective, home mitigation rates remain low. This study examines the barriers and facilitators to radon mitigation in homes from the perspectives of authorities responsible for radon risk management, the mitigation industry (contractors), and residents in four European countries (Belgium, Ireland, Slovenia, and the UK) with high radon risks and low mitigation rates. A multi-method approach was used to gather data from various stakeholders, including online surveys, content analysis of legal documents, group interviews, workshops, and focus groups.Authorities, contractors, and residents identified various facilitators to radon mitigation, including legal requirements for mitigation, awareness campaigns, low mitigation costs, availability of financial support, accreditation of mitigation contractors, and a perception of radon as a health threat. However, barriers to mitigation were also identified, such as a lack of awareness, fragmented mitigation processes, and inadequate communication between stakeholders. The study highlights the complexity of the radon mitigation process and suggests that interventions aimed at increasing mitigation rates should target stakeholders beyond just residents, such as constructors, health professionals, and policy makers. An integrated approach to radon mitigation, from policy to provision, is necessary to effectively lower levels of this indoor air pollutant.